Architectural drawing as simulation of the construction process (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2017)
This new digital season of our magazine opens up in a moment of big changes, so big that they make us think of a veritable revolution for Architecture. On the educational front we register a gradually increasing, though late, understanding of the need of a radical renewal of our teachings, in search of a better competitiveness for young Italian graduates on the international professional markets. Globalization induced on professional practice such a whirling acceleration and such unbelievable levels of complexity that traditional instruments and methods that have been efficiently working up to twenty or thirty years ago are now unsustainable and clearly obsolete. This new season of «XY» evidently opens to its readers at an extremely delicate moment: a big challenge for architectural scholars, for builders and, most of all, for teachers. The successful construction of a new paradigm will only be possible if its previous foundations will be re–discussed and courageously deconstructed. We are navigating towards a still unknown future.